Exploring the Landscape of Religiosity Research in Management: A Literature Review - Ganggali; Desman Hidayat (eCo-Fin, 2025)
Religiosity is a growing topic in management studies, yet a holistic review of its theoretical and empirical applications is lacking. This study addresses this gap by conducting a literature review of 18 quantitative studies from the SCOPUS database to analyze how religiosity is studied in the management sector. The review's objectives were to identify the background countries, management subject areas, underlying theories, and related variables of these studies. Findings indicate that research on religiosity is predominantly conducted in Indonesia, with a strong focus on Islamic-based concepts such as Halal and Shariah. The most common management area is marketing, followed by finance and human resources. The analysis reveals that behavior-related theories, particularly the Theory of Planned Behavior (TPB), are the most frequently used theoretical frameworks. Furthermore, religiosity is primarily examined as an independent or moderating variable, showing significant relationships with variables such as financial well-being, responsibility, engagement, and various marketing-related behaviors. This review provides a comprehensive overview of the current landscape of religiosity research in management and suggests opportunities for future studies.